Preserved endothelial progenitor cell angiogenic activity in African American essential hypertensive patients. (10th April 2017) - Kim, Seo Rin; Eirin, Alfonso; Herrmann, Sandra M S; Saad, Ahmed; Juncos, Luis A; Lerman, Amir; Textor, Stephen C; Lerman, Lilach O
Abstract: Background: African American (AA) subjects with essential hypertension (EH) have greater inflammation and cardiovascular complications than Caucasian EH. An impaired endogenous cellular repair system may exacerbate vascular injury in hypertension, yet whether these differ between AA EH and Caucasian EH remains unknown. Vascular repair by circulating endothelial progenitor cells (EPCs) is controlled by regulators of EPC mobilization, homing, adhesion and new vessel formation, but can be hindered by various cytokines. We hypothesized that EPC levels and function would be impaired in AA EH compared with Caucasian EH, in association with increased levels of inflammatory mediators and EPC regulators. Methods: CD3 4+ /KD R+ EPCs were isolated from inferior vena cava and renal vein blood samples of AA EH and Caucasian EH patients ( n  = 18 each) and from peripheral veins of 17 healthy volunteers (HVs) and enumerated using fluorescence-activated cell sorting. Angiogenic function of late-outgrowth endothelial cells expanded from these samples for 3 weeks was tested in vitro . Levels of inflammatory mediators, angiogenic factors and EPC regulators were measured by Luminex. Results: EPC levels were decreased in both AA and Caucasian EH compared with HVs, whereas their late-outgrowth endothelial cell angiogenic function was comparable. Levels of several inflammatory mediators were elevated in AA EH compared with Caucasian EH and HVs. Contrarily, vascular endothelial growth factor and its receptor-2 were lower. EPC levels inversely correlated with blood pressure in all hypertensive patients and estimated glomerular filtration rate with inflammatory mediators only in AA EH. Conclusions: Despite lower EPC numbers, decreased vascular endothelial growth factor signaling and inflammation, EPC function is preserved in AA EH compared with Caucasian EH and HVs, suggesting compensatory mechanisms for vascular repair.